Thin - Greenfield, Lauren (United States : HBO, 2006)
Eating disorders affect five million people in the U.S., and more than 10% of those diagnosed with anorexia nervosa will die from the disease. Seeking to put a human face on these sobering statistics, acclaimed photographer Lauren Greenfield went inside a Florida treatment center to tell the stories of four women who are literally dying to be thin. The devastating HBO documentary THIN reveals what she found there - and explores the issues underlying their illness.
Verzio Film Festival Submission
Duration: 01:42:00
Verzio Film Festival Submission
Keywords: Documentary films